The descriptive epidemiology of pre-omicron SARS-CoV-2 breakthrough infections and severe outcomes in Manitoba, Canada - Shaw, Souradet Y.; Kindrachuk, Jason; McKinnon, Lyle; Biegun, Jeffery C. S.; Reimer, Jocelyn N.; Loeppky, Carla; Wei, Yichun Joy; Bullard, Jared; Van Caeseele, Paul; Stein, Derek R. (Frontiers in Epidemiology, 2024)
Vaccination plays a key role in curbing severe outcomes resulting from COVID-19 disease. With the Omicron variant and the relaxing of public health protections breakthrough infections are increasingly common, and certain groups remain at higher risk for severe outcomes from breakthrough infections. We analysed population-based public health data from Manitoba, Canada to understand characteristics of those experiencing breakthrough infections and severe outcomes from breakthrough infections. Data from previous pandemic stages can provide valuable information regarding severe outcomes associated with breakthrough infection in the Omicron and future phases. Positive SARS-CoV-2 PCR tests from Cadham Provincial Laboratory were linked to case information from the population-based Public Health Information Management System. A retrospective design was used with time-to-event analyses to examine severe outcomes among those experiencing breakthrough infection. Breakthrough cases were more likely to have 2+ chronic conditions, compared to age-, sex-, and time-period matched unvaccinated cases (24% vs. 17%), with hypertension (30%), diabetes (17%), and asthma (14%) being the most prevalent chronic conditions amongst breakthrough cases. Severe outcomes resulting from breakthrough infection was associated with age and chronic conditions, with those with 2+ chronic conditions at higher risk of severe outcomes (adjusted hazard ratio: 3.6, 95% confidence intervals: 2.0-6.4). Risk of severe outcomes varied by age group, with those 70+ years at over 13 times the risk of severe outcomes (95% CI: 4.5-39.8), compared to those 18-29 years of age.